SELF-MEDICATION PRACTICES DURING COVID-19 PANDEMIC: A CROSS-SECTIONAL SURVEY - AHMAD MIR, SHAKEEL; SHAKEEL, DANISH; QADRI, ZULFKAR LATIEF (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Self-medication is a worldwide practice in which individuals, families, and/or communities choose pharmaceuticals to address health conditions without consulting a doctor. It impacts the health of people both negatively as well as positively. This study aims to determine the prevalence of self-medication for COVID-19 like symptoms during the pandemic. Methods: This is an online questionnaire-based survey on the perceptions and use of certain drugs for COVID-like symptoms during the COVID-19 pandemic. 168 people responded to the questionnaire. Results: Out of 168 respondents, 53.0% were males. 71.4% were below 30 years of age and, 25.6% were 31–60 years. The majority (72.6%) were unmarried. 50.0% had studied up to university level. 49.4% were unemployed. 39.9% were healthcare workers. 59.9% had suffered from respiratory symptoms during the COVID-19 pandemic. All those who developed symptoms had self-medicated. The most commonly used drugs were Paracetamol (85.0%), Azithromycin (58.0%), Expectorants (30.0%), Ivermectin (18.0%), Doxycycline (16.0%), Corticosteroids (7.0%), and Hydroxychloroquine (4.0%). The major sources of information about the disease and drugs were pharmacists (46.6%) and the internet (28.0%). Conclusion: There were significant percentages of self-medication during the COVID-19 pandemic, including the drugs without sufficient scientific evidence.